Genetic diversity and differentiation of the Critically Endangered Hispaniolan palm Coccothrinax jimenezii M.M. Mejía & R.G. García based on novel SSR markers. (June 2016) - Jestrow, Brett; Peguero, Brígido; Jiménez, Francisco; Cinea, William; Hass, Michael; Reeve, Andrew; Meerow, Alan W.; Griffith, M. Patrick; Maunder, Michael; Francisco-Ortega, Javier
Abstract: Coccothrinax jimenezii M.M. Mejía & R.G. García is a Critically Endangered palm species restricted to Haiti (one population near the city of Gonaïves with 43 individuals) and the Dominican Republic (one population on the shores of Lago Enriquillo with 18 individuals). The species faces two major conservation challenges: (1) water level rise in the hypersaline Lago Enriquillo and (2) overexploitation of leaves for making brooms in Haiti. Six SSR microsatellite loci were used to access levels of genetic variation and the genetic structure of these two populations. Only the Gonaïves site had loci that deviated from Hardy–Weinberg Equilibrium (2 loci). Both populations exhibited a relatively large number of private alleles (13 in Lago Enriquillo and 14 in Gonaïves) and did not show evidence of genetic bottlenecks. Inbreeding coefficients were much larger in Gonaïves ( F is = 0.232 ) than in Lago Enriquillo ( F is = 0.093 ). We detected high genetic differentiation among these sites ( F st = 0.497) suggesting that additional taxonomic studies are needed to determine if individuals from these two sites should be recognized as belonging to two different taxa. Because of taxonomic uncertainties we recommend not to translocate individuals between sites in future conservation activities involving this species. Highlights: Coccothrinax jimenezii is a Critically Endangered species restricted to Hispaniola. Six SSR loci were used to access genetic variation of its two known populations. A relatively large number of private alleles was detected. No evidence of genetic bottlenecks was found. High genetic differentiation among the two sites was detected.